Frontier capitalism and the expansion of rubber plantations in southern Laos - Laungaramsri P. (2014)
This article examines the recent expansion of large-scale rubber plantations in border areas of Laos and argues that this phenomenon as well as the attendant land concession controversy must be understood from the perspective of resource frontiers. While transnational Vietnamese investment in rubber plantations represents one form of land capitalisation, their establishment in southern Laos has been part of the turbulent political economic transition in Laos. Collaboration between frontier states which often bypasses central governance, chaotic boundaries between what is recognised as 'used or productive-and 'unused or underproductive resources-, and regulatory disorientation of resource control allow what I call 'frontier capitalism-to proliferate. © 2012 The National University of Singapore.